The Effect of Using the Quizizz Application on the Learning Outcomes of the Cognitive Domain of Grade V Elementary School Students on the Animal Respiratory System - Satria Adlan Hakim; Gunta Wirawan; Rini Setyowati; Hikaru Toda (Variabel, 2023)
This study aimed to determine the effect of using the Quizizz application on the learning outcomes of the cognitive domain of grade V elementary school students on the animal respiratory system. The type of research used was quantitative research with a quasi-experimental design in the form of a nonequivalent control group design. The population of this study was all grade V elementary school students totalling 74 students. Samples were taken by convenience sampling technique consisting of the VA class with 25 students as the experimental class and the VC class with 24 students as the control class. Data collection was carried out using cognitive learning outcomes tests on the animal respiratory system. The data were then analyzed using an independent two-sample t-test, an Effect Size test, and an N-gain test. The results showed that: (1) there were differences in student cognitive learning outcomes between classes that used the Quizizz application and classes that did not use the Quizizz application with tcount > ttable, namely 3.8133 > 2.0139; (2) the use of the Quizizz application had a high influence on the learning outcomes of the cognitive domain of students with the results of an Effect Size of 1.08, high criteria; (3) the use of the Quizizz application could improve students' cognitive learning outcomes with N-gain results of 0.5172, medium criteria. Thus, it could be concluded that there was an effect of using the Quizizz application on the learning outcomes of the cognitive domain of grade V elementary school students on the animal respiratory system.